Atomically Dispersed CoN3C1‐TeN1C3 Diatomic Sites Anchored in N‐Doped Carbon as Efficient Bifunctional Catalyst for Synergistic Electrocatalytic Hydrogen Evolution and Oxygen Reduction. Issue 29 (5th June 2022) - Wang, Minmin; Zheng, Xiuhui; Qin, Donglin; Li, Min; Sun, Kaian; Liu, Chuhao; Cheong, Weng‐Chon; Liu, Zhi; Chen, Yanju; Liu, Shoujie; Wang, Bin; Li, Yanpeng; et al.
Abstract: A encapsulation–adsorption–pyrolysis strategy for the construction of atomically dispersed Co‐Te diatomic sites (DASs) that are anchored in N‐doped carbon is reported as an efficient bifunctional catalyst for electrocatalytic hydrogen evolution reaction (HER) and oxygen reduction reaction (ORR). The as‐constructed catalyst shows the stable CoN3 C1 ‐TeN1 C3 coordination structure before and after HER and ORR. The *OOH/*H intermediate species are captured by in situ Raman and in situ attenuated total reflectance‐surface enhanced infrared absorption spectroscopy, indicating that the reactant O2 /H2 O molecule has a strong interaction with the Co site, revealing that Co δ+ is an effective active site. Theoretical calculations show that the Co δ+ has adsorption‐activation function and the neighboring Te δ+ acts as an electron donor adjusting the electronic structure of Co δ+, promoting the dissociation of H2 O molecules and the adsorption of H and oxygen‐containing intermediates in HER and ORR. In the meanwhile, the nearest C atom around Co also profoundly affects the adsorption of H atoms. This results in the weakening of the OH adsorption and enhancement of H adsorption, as well as the more stable water molecule dissociation transition state, thus significantly boosting ORR and HER performance. Abstract : The Co‐Te diatomic sites (DASs) with special CoN3 C1 ‐TeN1 C3 coordination structure anchored in N‐doped carbon are constructed by an encapsulation–adsorption–pyrolysis strategy, which serves as an efficient bifunctional catalysts for synergistic electrocatalysis of HER and ORR. This work provides numerous new opportunities for the rational design and artificial synthesis of DASs catalysts for energy conversion.